2007
DOI: 10.1167/iovs.06-1258
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-Dependent Apoptosis in Light-Induced Retinal Degeneration

Abstract: In the authors' model of retinal degeneration, photoreceptor cells die through a caspase-dependent mechanism. However, the molecular events involved during and after light exposure seemed to implicate different proteases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
6
32
1
Order By: Relevance
“…In both inherited retinal degeneration and light-induced retinal degeneration, caspase-3 inhibitors showed a protective effect, suggesting that photoreceptor degeneration is related to caspase-3 activation (Perche et al, 2007(Perche et al, , 2008. For these reasons, we confirmed that caspase-3/7 was activated by light injury, being significant at 48 h after light exposure.…”
Section: Discussionsupporting
confidence: 73%
“…In both inherited retinal degeneration and light-induced retinal degeneration, caspase-3 inhibitors showed a protective effect, suggesting that photoreceptor degeneration is related to caspase-3 activation (Perche et al, 2007(Perche et al, , 2008. For these reasons, we confirmed that caspase-3/7 was activated by light injury, being significant at 48 h after light exposure.…”
Section: Discussionsupporting
confidence: 73%
“…These inhibitors have been used and tested extensively to study the apoptotic pathways in retinal degeneration models (44,45). In separate experiments (n ϭ 6 retinas each; 3 independent experiments), 2 L of 12.5 mM NMDA plus 2 L of 2 mM of caspase-1 or caspase-3 inhibitor were injected into the vitreous, followed by TcapQ as described.…”
Section: Procedures Of In Vivo Intravitreal Injectionmentioning
confidence: 99%
“…Conventional cultured retinas exhibited similar expression pattern of cleaved caspase-3, indicating that this apoptotic pathway does not contribute to photoreceptor apoptosis in the porcine retina following culture and low-intensity illumination. Even though only periodic low-intensity illumination was tested in the current study, it is known that different apoptotic pathways can be induced depending on light intensity and duration in rodent models (Contin et al, 2013;Hao et al, 2002;Perche et al, 2007).…”
Section: Opsin Accumulation and Cyclic Illumination Promote Er-stressmentioning
confidence: 99%